DIMENSIONS OF FAMILY LEVEL STRUCTURE IN THE INCIDENT OF CHILD MARRIAGE IN BOGOR REGENCY - Nurul Amirah; Ekawati Sri Wahyuni; Tin Herawati (Sodality: Jurnal Sosiologi Pedesaan, 2025)
Child marriage is a social problem that is still a concern, especially in Bogor Regency. This study aims to analyze the structural dimensions at the family level that contribute to the incidence of child marriage in Bogor Regency. The approach used is a quantitative approach supported by a qualitative approach through in-depth interviews, observation, and statistical data analysis. The research sample consisted of 90 women who married before the age of 19 within the last 10 years, selected using purposive sampling technique. The research was conducted in Kertajaya Village, Rumpin Sub-district, West Java Province. The results showed that there are two communities in Kertajaya Village, namely the aspect community and the dospek community. Based on Giddens' structure theory, three dimensions were found, namely 1) significance interprets marriage as social stability, cultural and religious values, 2) domination can be seen from the strong control of parents, especially fathers, in decision-making and the limited autonomy of children; and 3) legitimacy appears when this practice is considered socially and religiously valid, even though it is against the law. The family acts as both a norm-preserving structure and a decision-making agent for child marriage.